Enhanced Transgene Expression by Optimization of Poly A in Transfected CHO Cells - Wang, Xiao-yin; Du, Qiu-jie; Zhang, Wei-li; Xu, Dan-hua; Zhang, Xi; Jia, Yan-long; Wang, Tian-yun (Frontiers in Bioengineering and Biotechnology, 2022)
The generation of stable, high-level recombinant protein-producing cell lines remains a significant challenge in the biopharmaceutical industry. Expression vector optimization is an effective strategy to increase transgene expression levels and stability, and poly A elements play a significant role in this process. In this study, we investigated the effects of different poly A sequences on transgene expression in Chinese hamster ovary (CHO) cells. Five poly A elements, including bovine growth hormone (BGH), mutant BGH, herpes simplex virus type 1 thymidine kinase (HSV-TK), SV40, and a synthetic (Synt) poly A, were cloned into the pIRES-EGFP vector and transfected into CHO cells. Results indicated that vectors containing the SV40 and Synt poly A sequences offer significant improvements in stable and long-term stable transgene expression. However, qPCR results demonstrated that the transgene expression level was not related to the gene copy number and mRNA level in stable transfected CHO cells. Importantly, the SV40 and Synt poly A sequences decreased the variation of expression. Furthermore, adalimumab expression also showed that the SV40 and Synt poly A sequences induced higher protein levels. In conclusion, SV40 poly A and Synt poly A are strong poly A elements that increase stable transgene expression and decrease the variation of expression, and polyadenylation sequences should be taken into consideration in the design of recombinant protein expression vectors.